Effect of Temperature on the Mechanical Properties and Deformation Mechanism of a High Mn Steel With Composite Structure - Chen, Xiaoman; Wang, Yuhui; Xiong, Jianchao; Li, Guoyang; Tian, Yanzhong; Cao, Wenquan; Wang, Tiansheng (Frontiers in Materials, 2020)
A composite high manganese structure comprising recovered and recrystallized structures was prepared using a single-phase austenitic Fe-30Mn-0.14C-7Cr-0.26Ni steel by cold rolling and annealing. The yield strength and elongation of the composite increased simultaneously, when the tensile temperature decreased from room temperature (RT) to low temperature (−180°C). The composite structure exhibited a good combination of strength and ductility at RT and −180°C. The notable mechanical properties at low temperature can be attributed to the enhanced strain-hardening capability via introducing multiple deformation mechanisms in the composite structure.